토픽모델링을 이용한 태권도 시범 연구 동향분석: 2004년부터 2023년까지 - 조혜수; Hyesoo Cho; 박지용; Jiyong Park; 이은수; Eunsu Lee (Ch'eyuk kwahak yŏn'gu, 2024)
[목적] 본 연구는 태권도 시범(격파 & 공연)에 대한 그 동안에 연구동향을 분석함으로서 시의성을 제공하고, 향후 연구에 새로운 통찰력을 제공하는데 목적이 있다. [방법] 2004년 4월부터 2023년 4월까지 태권도 시범을 키워드로 한 총 20년 총 425편의 논문에 국문초록을 분석 대상으로 선정하였으며, Python3.5.2를 사용하여 Dynamic Topic Modeling(LDA)과 구간별 토픽점유율과 연도의 상관관계 분석을 실시하였다. [결과] Dynamic Topic Modeling(LDA)결과 Topic 1(10%): ‘시범의 공연 문화예술로서의 발전’, Topic 2(11%): ‘시범경기의 판정 및 규칙 발전’, Topic 3(08%): ‘교육과정 개발과 지도자의 전문성’, Topic 4(11%): ‘기술적 움직임 및 운동학적 특성’, Topic 5(09%): ‘시범공연 마케팅 및 관람’, Topic 6(19%): ‘선수의 심리적 요소와 훈련 및 경기 성과’, Topic 7(33%): ‘세계화와 국제적 발전과 교류’로 나타났다. 구간별 토픽점유율과 연도 간 상관관계 분석결과 Topic 1~5까지는 통계적으로 유의미한 상관관계가 나타나지 않았으나, Topic 6인 ‘대학 선수들의 훈련과 정서’는 통계적으로 매우 유의미하였으며 양의 상관관계가 나타났다. Topic 7인 ‘세계화와 국제적 발전과 교류’의 경우 통계적으로 매우 유의미하였으며 음의 상관관계가 나타났다. [결론] 향후 연구에서는 특정 기술 수행에서 선수들의 정서 관리와 선수들의 훈련방식에 관한 연구에 더욱 집중할 필요가 있으며, 태권도의 국제적인 성격을 감안한 연구가 추가로 요구될 수 있다. PURPOSE By analyzing trends in Taekwondo demonstrations, specifically in breaking and performances, to date, this study aims to offer timely insights and set the groundwork for future research. METHODS We used Korean abstracts from a total of 425 papers containing the keyword “Taekwondo demonstrations” spanning 20 years from April 2004 to April 2023. We employed Python 3.5.2 to conduct dynamic topic modeling (Latent Dirichlet Analysis, LDA) and to examine the correlation between the topic distribution by section and the publication year. RESULTS The main findings from the LDA are as follows. Topic 1 (10%): “The development of demonstrations: performance in culture and art, ” Topic 2 (11%): “The development of formalized rules and judgments in a demonstration event,” Topic 3 (08%): “A study on the educational courses and professionalism of Taekwondo coaches,” Topic 4 (11%): “Technical movements and kinematic characteristics,” Topic 5 (09%): “A study on marketing perspectives of demonstration performances,” and Topic 7 (33%): “Global exchange: the development and rise of internationalization.” In the correlation analysis between the topic share by section and the publication year, Topics 1 to 5 exhibited no statistically significant correlation. However, Topic 6, “A study on the attainment of events, training, and the psychological factors influencing athletes” and Topic 7, “Global exchange: the development and rise of internationalization,” also displayed a very statistically significant but negative correlation. CONCLUSIONS Future research should focus on studies on the psychological management of athletes during the performance of specific techniques and training methods. Further research considering the global characteristics of Taekwondo may be required.